Modelling the yield and profitability of intercropped walnut systems in Croatia - Žalac, Helena; Burgess, Paul J.; Graves, Anil; Giannitsopoulos, Michail; Paponja, Ivan; Popović, Brigita; Ivezić, Vladimir (Springer, 2021)
In Croatia, farmers are showing increasing interest in establishing walnut orchards for nut production on arable land due to higher anticipated net margins. One way to address the lack of profitability in the initial years when nut yields are low may be to plant arable intercrops. The anticipated impacts of this practice were assessed using a biophysical simulation model (Yield-SAFE) to determine the growth and yield of crops and trees in arable, orchard, and silvoarable systems, and an economic farm model (Farm-SAFE) was used to assess their profitability. The walnut orchard and the intercropped orchard systems were simulated assuming tree densities of 170, 135, and 100 trees ha−1, to determine the profitability and break-even date of the systems. The biophysical simulation predicted a decline in arable intercrop yields over time in all tree density scenarios. However, analysis of productivity of intercropped systems showed that intercropping was more productive than separate arable and walnut production for all tree density scenarios. From financial aspect, the return from intercropping helped to offset some of the initial orchard establishment costs and the arable intercrop remained profitable until the sixth year after tree planting. The modelling predicted that a system with 170 trees ha−1 that included intercropping for the first 6 years provided the greatest cumulative net margin after 20 years. The financial benefit of intercropping over the first 6 years opposed to monoculture walnut fruit production appeared to be consistent across the three tree densities studied. These results suggest that silvoarable agroforestry is profitable approach to establishing walnut orchards.
Keywords: Orchard; Walnut; Intercropping; Silvoarable agroforestry; Bio-economic model